Message Security on Chat App based on Massey Omura Algorithm - Taronisokhi Zebua; Rivalri Kristianto Hondro; Eferoni Ndruru (IJISTECH (International Journal of Information System and Technology), 2018)
Security of message on chat apps is very important to do so that messages that distributed always safety for others who do not have access permission. However, not all chat apps currently have tools that used to secure messages. This is still often overlooked, thus providing an easy space for the attackers to hack messages that are distributed. This research explains the usage of the massey-omura algorithm to secure text type message in chat apps when message distributed